The Reformation and Covenant Theology (Edmonton, AB Canada : Still Waters Revival Books, 2002)
Knox, John Calvin, John Covenanted General Assembly of the Church of Scotland The Westminster Assembly The Reformed Presbytery in North America (RPNA) Rutherford, Samuel Renwick, James Henderson, Alexander Brown, John (of Wamphray) Shields, Alexander Brown, John (of Haddington) Flavel, John Cunningham, John Witsius, Herman Boston, Thomas Gillespie, Patrick Gillespie, George Symington, William Fraser, James (of Brae) Mason, Archibald Roberts, William L. Price, Greg Barrow, Greg Barrow, Reg